Genetic diversity of broad beans (Vicia faba) in the collection of the Vavilov Institute and its use in breeding - S. M. Mamedova; M. A. Vishnyakova (Труды по прикладной ботанике, генетике и селекции)
The paper presents brief information about the history of the collection of broad (horse) beans (Vicia faba L.) at the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR), its composition, research trends, and significance for domestic breeding. The collection started in 1916 with Vavilov’s collecting activities in the Pamirs. Currently, the collection consists of 1733 accessions from 67 countries, obtained from foreign genebanks through germplasm exchange and seed requests, received from domestic and foreign breeders, and collected in numerous expeditions. Broad beans are used for food (vegetable) and feed; they are adapted to a wide range of latitudes and altitudes. A larger part of the collection is represented by fodder accessions. The main principle whereupon the collection is being augmented is the priorities of domestic breeding. The paper provides information on the botanical, environmental and geographical diversity of VIR’s broad bean collection, its level of studiedness, current research issues, and the use of the collection in the breeding process. The crop’s biological traits, characteristics of vegetable and fodder accessions, current breeding trends and source material for breeding are described. A brief analysis of the current status of broad bean breeding in Russia and VIR’s contribution to this process is presented, including the Institute’s direct involvement in the development of several cultivars of both feed and food uses. Presently, 30 broad bean cultivars are listed in the State Register of Breeding Achievements of the Russian Federation, and 28 of them are the products of domestic breeding.